The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.14202/vetworld.2015.1150-1155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium supplementation on performance, cost economics, and biochemical profile of Nellore ram lambs

Abstract: Aim:Present experiment was conducted to investigate the effect of selenium (Se) supplementation on performance, carcass characteristics, meat composition, shelflife of meat and biochemical profile in Nellore ram lambs.Materials and Methods:24 male Nellore ram lambs (15.75±0.47 kg) were randomly divided into four dietary groups with six lambs in each and reared under uniform management conditions for 120 days. Basal diet was not supplemented with Se and consisted of green fodder (Se 0.09 mg/kg dry matter [DM]),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…To our knowledge, several studies have been conducted on the effect of Se on performance. Ghaderzadeh (2016) reported that supplementation of nano-selenium to Moghani male lambs had no significant effect on performance, which is in accordance with other studies that have been done on other (Sushma et al, 2015) and beef calve (Richards et al, 2011). Therefore, the insignificant difference in these studies might be due to feeding the balanced diet with adequate nutritional practice where Se is not deficient.…”
Section: Initial Body Weight (Ibw) Final Body Weight (Fbw) Body Weisupporting
confidence: 72%
“…To our knowledge, several studies have been conducted on the effect of Se on performance. Ghaderzadeh (2016) reported that supplementation of nano-selenium to Moghani male lambs had no significant effect on performance, which is in accordance with other studies that have been done on other (Sushma et al, 2015) and beef calve (Richards et al, 2011). Therefore, the insignificant difference in these studies might be due to feeding the balanced diet with adequate nutritional practice where Se is not deficient.…”
Section: Initial Body Weight (Ibw) Final Body Weight (Fbw) Body Weisupporting
confidence: 72%
“…In a study by Mohri et al [ 55 ], Se and vitamin E supplements did not affect the final BW or ADG of lambs. Alimohamady et al [ 56 ], Sushma et al [ 57 ], and Vignola et al [ 58 ] found that Se supplementation did not influence growth performance in lambs. Selenium also did not considerably affect the growth rate of buffalos [ 59 ], or ADG, feed intake, and feed conversion in goats [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated the effects of selenium supplementation on body weights in chickens [43], lambs [44], cows [45], and also in laboratory animals like rats [46] and mice [13]. The results are diverse depending on the concentration, duration, and source of selenium.…”
Section: Discussionmentioning
confidence: 99%